OP0157 HPR EUROPEAN PATIENT VOICE IN GOUT SURVEY – SUBJECTIVE SATISFACTION IN GOUT PATIENTS VERSUS OBJECTIVE SUBOPTIMAL GOUT CARE. (June 2019) - Meulemeester, Marc De; Jansen, Tim; Petersen, Gudula; Perez-Ruiz, Fernando
Abstract : Background: Gout is the most common form of inflammatory arthritis with an increasing prevalence and incidence in many countries (1). Few information is available about current management of gout and satisfaction of patients living with gout. Objectives: To evaluate diagnosis and treatment of gout from patient perspective to improve treatment outcomes for gout patients in Europe. Methods: A 15 minute online survey with gout patients from 14 European countries (Austria, Belgium, France, Denmark, Germany, Italy, Ireland, Malta, Netherlands, Norway, Portugal, Spain, Sweden, Switzerland) was conducted in 2018. The design and content of the survey has been developed together with several patient and clinical experts Results: 1, 100 gout patients (78% males, mean age 55 years) with a mean number of 2.9 flares in the past 12 months completed the survey. 77% percentage of patients are suffering from co-morbidities (hypertension 52%, dyslipidemia 41%, overweight 40%, type 2 diabetes 23%, long-term illness of kidney/renal insufficiency 17%). It was reported that mainly general practitioners are involved in the diagnosis of the disease (73%), discussion of gout (68%) and treatment of last gout flare (59%), whereas rheumatologists are less involved in diagnosis (8%), discussion (15%) and treatment (11%) of last gout flare. 22% of patients were not diagnosed until they have had 4 or more flares. 71% of patients had flares in the past 12 months (thereof 33% ≥3 flares) which seemed to be particularly an issue for younger patients. 58% of patients receive uric acid lowering therapies, 43% pain killers, 25% colchicine, 13% non-medical pain relief and 12% corticosteroids. 59% of patients do not have regular follow up appointments for their gout and 53% are monitored for serum uric acid less than twice per year. But 79% of patients claim to be satisfied with their current treatment and do not expect better management of their disease. Conclusion: The results of the survey demonstrate that gout patients in Europe are diagnosed late, their disease is not well controlled and not regularly monitored. It seems that their doctors are not aware of the pain and impact of gout on their patients' quality of life as patients are not telling them about it. Nevertheless, most of the patients feel their current treatment is the best they can get. There is a clear need to educate patients and their doctors about adequate management of gout. Reference: [1] Kuo C-F, Grainge MJ, Zhang W, Doherty M. Global epidemiology of gout: prevalence, incidence and risk factors. Nat Rev Rheumatol. 2015 Nov;11(11):649–62. Acknowledgement: The survey was conducted by Hall & Partners and funded by Grünenthal. Disclosure of Interests: Marc De Meulemeester Consultant for: Grünenthal, Speakers bureau: Novartis, Astra Zeneca, Tim Jansen Grant/research support from: Olatec, Consultant for: Abbvie, Celgene, Menarini, Novartis, Speakers bureau: Grünenthal, Gudula Petersen Employee of: Grünenthal, Fernando Perez-Ruiz Grant/research support from: Cruces Rheumatology Association, Consultant for: Grunenthal, Menarini, Horizon, Speakers bureau: Menarini, Grunenthal; Spanish foundation for rheumatology